REGARDING THE ISSUE OF WELLS DIAGNOSTICS OF UNDER-GROUND GAS STORAGE BASED ON FILTRATION RESISTANCE COEFFICIENT - Vladimir A. Vasiliev; Tatyana A. Gunkina; Petr N. Livintsev; Olga Yu. Turskaya (Вестник Северо-Кавказского федерального университета, 2022)
The item offers a view on the diagnostics of wells in underground gas storage based on filtration resistance coefficient. There is also a presentation and comparison of the outcomes of calculation for the wells of Kasimivsky underground gas storage with gravel filter.